2016
DOI: 10.1039/c6ra20692a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CuSbSe2crystallites synthesized using a hot injection method

Abstract: In this study, a novel and facile hot injection method for the synthesis of single phase CuSbSe2 crystallites was developed by using low toxic triethylene glycol as both the solvent and reducing agent and triethylenetetramine as co-reducing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…[20][21][22][23] Therefore, the prepared Sb 2 Se 3 film also contains some Sb 2 O 3 and elemental Se components, which may result from the slight oxidation of Sb at the surface of crystallites. 24 It is believed that these components may passivate the defects (selenium vacancy) and profit the device performance. 25 The Sb 2 Se 3 film was employed to fabricate photodiode detector with a structure of ITO/SnO 2 /Sb 2 Se 3 /Au, where the spin-coated SnO 2 film is used as the buffer layer.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23] Therefore, the prepared Sb 2 Se 3 film also contains some Sb 2 O 3 and elemental Se components, which may result from the slight oxidation of Sb at the surface of crystallites. 24 It is believed that these components may passivate the defects (selenium vacancy) and profit the device performance. 25 The Sb 2 Se 3 film was employed to fabricate photodiode detector with a structure of ITO/SnO 2 /Sb 2 Se 3 /Au, where the spin-coated SnO 2 film is used as the buffer layer.…”
Section: Resultsmentioning
confidence: 99%
“…Sb 2 Se 3 is a p-type semiconductor that exhibits low electrical conductivity with an excellent photoresponse [32][33][34], and crystallizes in a one-dimensional structure where the ribbons are held together by van der Waals forces [35]. This structure contributes to poor carrier transport and mobility between the ribbons [36] with various reported band gaps in the range of 1.2-1.8 eV [37,38]. The XRD pattern of the annealed thin film with 17 W of sputtering power does not show any dominant peak, but there are many peaks with low intensity, as shown in Figure 3c.…”
Section: Resultsmentioning
confidence: 99%
“…[65] Recently, Liu et al have explained synthesis of colloidal Cu 3 SbSe 3 NCs by using highly reactive phosphine free Se precursor and hot injection method. [66] Employing facile novel hot injection method and using triethylene glycol (TEG) as solvent as well as reducing agent, single phase CuSbSe 2 NCs have been synthesized by Hsinag et al [67] Mechanical alloying was employed by Zang et al to synthesize single phase CuSbSe 2 chalcostibite for the first time which showed enhancement in thermoelectric property. [68] Limited reports on the synthesis of CuÀSb-Se compounds opened avenues for chemists to indulge in the chemical synthesis for better control over size, shape, purity and stoichiometry employing alternate precursors and experimental strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu et al have explained synthesis of colloidal Cu 3 SbSe 3 NCs by using highly reactive phosphine free Se precursor and hot injection method . Employing facile novel hot injection method and using triethylene glycol (TEG) as solvent as well as reducing agent, single phase CuSbSe 2 NCs have been synthesized by Hsinag et al Mechanical alloying was employed by Zang et al to synthesize single phase CuSbSe 2 chalcostibite for the first time which showed enhancement in thermoelectric property …”
Section: Introductionmentioning
confidence: 99%